2014
DOI: 10.1037/a0032782
|View full text |Cite
|
Sign up to set email alerts
|

Deployment-related sequelae and treatment utilization in rural and urban war veterans in Hawaii.

Abstract: This study compared common deployment-related health issues and correlates of mental health service utilization among rural and urban veterans of Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), and Operation New Dawn (OND) living in Hawaii. Frequency of utilization of a broad range of mental health resources, including clergy/spiritual leaders, videoconference/online programs, and traditional/alternative healers, was also characterized. A random sample of 116 rural and 117 urban ethnoracially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 61 publications
1
45
0
Order By: Relevance
“…In a similar population of 116 rural and 117 urban veterans who served in OEF/OIF/OND, Whealin et al found rural veterans were less educated (high school or less: 30 vs. 12%, college degree: 17 vs. 30%), more likely to screen positive for PTSD (43 vs. 30%), have postconcussive (41 vs. 24%), and alcohol use problems (20 vs. 8%). 38 Utilization of VA services including medications and mental health were comparable between rural/urban groups (40%/32%). The authors contend that economic and community resources can buffer the impact of stress-related disorders.…”
Section: Management Care and Costmentioning
confidence: 93%
See 3 more Smart Citations
“…In a similar population of 116 rural and 117 urban veterans who served in OEF/OIF/OND, Whealin et al found rural veterans were less educated (high school or less: 30 vs. 12%, college degree: 17 vs. 30%), more likely to screen positive for PTSD (43 vs. 30%), have postconcussive (41 vs. 24%), and alcohol use problems (20 vs. 8%). 38 Utilization of VA services including medications and mental health were comparable between rural/urban groups (40%/32%). The authors contend that economic and community resources can buffer the impact of stress-related disorders.…”
Section: Management Care and Costmentioning
confidence: 93%
“…In OEF/OIF/OND veterans, morbidity rates have been reported at 60% higher rates than from soldiers in cities and suburbs. 38…”
Section: Management Care and Costmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, fewer than half of those who have deployed and report symptoms indicating that they could benefit from mental health services actually receive such care (Gorman et al, 2011;Pietrzak et al, 2009;Schell and Tanielian, 2011). There is some evidence that greater symptom severity increases treatment-seeking (Balderrama-Durbin et al, 2013;Cohen, Gima, et al, 2010;Possemato et al, 2010;Whealin et al, 2014). Some of the more commonly endorsed reasons about why those who might benefit from treatment don't get it are: difficulty scheduling an appointment or getting time off, stigma, and treatment costs Elnitsky et al, 2013;Schell and Tanielian, 2011).…”
Section: Mental Health Servicesmentioning
confidence: 99%